A Platonic Critical Study of TV as a Poet - Hassan Ahmadizadeh (Journal of Philosophical Investigations, 2021)
The quarrel between Plato and the poets in the Utopia and try to exclude them from there is a very important subject in the Republic. He in the book III explains the limits for poems and determines the poems that can be read for youths and the poems that cannot be read for them. This radical Platonic approach to the poets and their poems can be linked today to the many different media especially TV and its programs. In Plato's view, our reaction to the different events in the everyday life is a copy of our reaction to the poem. This problem is today linked to the TV and other social media like cinema. TV in only an instrument for distribution and transmission, and does not present any new method for interpreting reality. In another word, TV only present reality as it is and TV is like the Platonic poet in this respect. We can recite the Platonic objection on poem, also on the TV and its functions. In the present article we will try to survey the nature and the functions of TV by the Platonic method of critiquing poets in the Utopia.